2021
DOI: 10.1016/j.pbi.2021.102012
|View full text |Cite
|
Sign up to set email alerts
|

Digital paradigm for Polycomb epigenetic switching and memory

Abstract: How epigenetic memory states are established and maintained is a central question in gene regulation. A major epigenetic process important for developmental biology involves Polycomb-mediated chromatin silencing. Significant progress has recently been made on elucidating Polycomb silencing in plant systems through analysis of Arabidopsis FLOWERING LOCUS C ( FLC ). Quantitative silencing of FLC by prolonged cold exposure was shown to represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Specifically, PcG-protein-mediated histone modifications and epigenetic silencing of the main floral inhibitor FLC are the central hub in the control of vernalization, which is conserved in several plant species [188]. Studies regarding epigenetic regulation of the FLC locus have been thoroughly discussed in several reviews [175,[189][190][191], and will not be discussed here.…”
Section: Seasonal and Diel Oscillationsmentioning
confidence: 99%
“…Specifically, PcG-protein-mediated histone modifications and epigenetic silencing of the main floral inhibitor FLC are the central hub in the control of vernalization, which is conserved in several plant species [188]. Studies regarding epigenetic regulation of the FLC locus have been thoroughly discussed in several reviews [175,[189][190][191], and will not be discussed here.…”
Section: Seasonal and Diel Oscillationsmentioning
confidence: 99%
“…One such example is PRC2-mediated regulation at the Arabidopsis floral repressor gene FLOWERING LOCUS C ( FLC ) (Menon et al, 2021). The winter cold-induced epigenetic silencing is an ON/OFF cell-autonomous, stochastic switching of individual FLC copies into a Polycomb silenced state (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged exposure to cold temperature, also referred to as vernalization, provides a direct link between environmental sensing and the establishment and resetting of an epigenetic somatic memory to regulate flowering initiation in arabidopsis (Arabidopsis thaliana). Elegant genetic and modeling studies on flowering regulation have uncovered a distinct temperature sensing mechanism where vernalization operates via a digital, polycomb-mediated epigenetic switch leading to the upregulation of VERNALIZATION INSENSITIVE3 (VIN3) and silencing of FLOWERING LOCUS C (FLC) [28]. In addition, recent reports showed that the epigenetic memory of vernalization is meiotically stable during female gamete formation and is maternally transmitted in arabidopsis before being reset during embryogenesis.…”
Section: Interplay Between Stress-induced Epigenetic Changes and Stre...mentioning
confidence: 99%